KAJIAN SEMIOTIKA ROLAND BARTHES TENTANG AZAB KAUM SODOM - Nurhasanah, Nurhasanah (UIN Imam Bonjol Padang, 2023)
The verses that talk about the doom of the sodomites at the time of the Prophet Luth As in the Qur'an. However, the verses are not written textually or literally with the word